International Standards for the Professional Practice of Internal Auditing – Remarks on Implementing Them in Local Government Units - Walenia, Alina (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
The aim of the article is an attempt to assess the International Standards for the Professional Practice of Internal Auditing in the process of organisation and audit activities in the entities from the public finance sector. The analysis was conducted based on a selected group of standards that are particularly significant in the process of efficiency and effectiveness of audit activities due to the limited text of this article. The introduced Standards define the framework rules of performing and promoting a broad scope of internal audit services adding value to an organisation. Moreover, the purpose of the Standards is to create the basis for the assessment of internal audit activities, thence the facilitation of the processes and operating activities of an organisation. Internal audit is one of the key elements necessary for the proper management of an organisation, including a public finance sector unit. In line with the definition of The Institute of Internal Auditors (IIA), internal auditing is an independent, consulting and verifying activity designed to improve organization’s operations and to add value to it. Internal audit supports an organisation in achieving its goals through a systematic and methodical approach to the assessment and improvement of the processes of risk and organisation management as well as control.